Modelling and dynamic analysis of vehicles based on discrete constraints. (2017) - Shao, Ke; Huang, Kang; Duan, Songlin; Zhen, Shengchao; Gao, Feng
In this paper, a novel approach to modelling and dynamic analysis of full vehicle is proposed based on Udwadia-Kalaba theory. Because the vehicle is hierarchically modelled by using this approach, this approach is easily processed when handling the modelling of many-degrees-of-freedom vehicle. Also, the analytical dynamic model based on this approach is free of calculation of Lagrangian multiplier as used in the Lagrangian equation. To verify this approach, a 15 DOF vehicle is modelled in this paper by using Udwadia-Kalaba theory. Four tyres' displacement is exerted and the vertical dynamic behaviour of each subsystem is simulated and analysed in MATLAB. By solving Udwadia-Kalaba equation, the response of each subsystem is acquired. The simulation result is well coincident with that of the Lagrangian model, which verifies the proposed approach.